Thermodynamic Analysis of Steam Gasification for Syngas Production in Biomass Renewable Energy Using Parametric Investigation - Ziyu Wang; Charalampos Baniotopoulos (Advances in Engineering and Intelligence Systems)
The need for renewable energy sources has increased due to pollution caused by fossil fuels and increased energy demand. Biomass is considered as a clean renewable energy source that releases zero carbon dioxide. But it is not common to use it because of its low energy density. Therefore, it is converted into syngas using processes such as gasification. Gibbs free energy minimization approach is used in this investigation. This study has investigated the impcats of biomass flow rate, temperature of gasification, and steam flow rate on mole fraction and mass flow rate of carbon monoxide, hydrogen, carbon dioxide, methane and steam gases. Also, the amount of heat consumed or produced in drying, pyrolysis and Gibbs reactors was also studied in this investigation. According to the results, an enhancemment of 13.8% in hydrogen molar fraction can be observed with increasing gasification temperature from 700℃ to 900℃. Steam flow rate and biomass flow rate have a noticeable effect on the quality of syngas. As biomass flow rate increases, the heat consumed in the drying reactor increases and the heat produced in the pyrolysis reactor increases. As the steam flow rate increases, the heat consumed in the Gibbs reactor increases. Also, the hydrogen mole fraction is maximum at a steam mass flow rate of 5000 kg/h and biomass flow rate of 1000kg/h.